The possible cytotoxicity developed by the use of ivermectin in patients with COVID-19: an integrative review (Research, Society and Development, 2022)
Objective: To analyze the scientific literature that deals with the possible cytotoxicity developed by the use of ivermectin in patients with COVID-19: an integrative review. Methods: This is an integrative literature review, designed as an observational, cross-sectional and qualitative study, data collection was carried out from recent literary and scientific sources, from the year 2020 to the year 2022. Results: Ivermectin is metabolized in the liver, has a half-life four times longer than other drugs, and has great hepatoxic potential. Scientific evidence for its use was based on in vitro research, which shows insufficient results to determine its safety and efficacy. It was found that 05 days of treatment with ivermectin was a safe time to show effective results, with a dose of 0.4 - 0.6mg/kg per day. The interactions of ante - COVID 19 drug candidates with hepatic transporters were identified, these drugs have multiple inhibitory effects on hepatic membrane transporters and can cause toxicity and affect pharmacokinetics. Conclusion: The imprecision of data on the therapeutic use of ivermectiva is evidenced, together with low quality information for clinical guidance, with regard to use, dosage and duration of treatment. As for the possible cytotoxic effect of Ivermectin in patients with covid-19, there were no clinical studies to show such a result, however, its use is contraindicated due to the scarcity of data. Therefore, further randomized clinical trials are needed to determine the level of toxicity of ivermectin in the treatment of SARS-CoV-2.